THE EFFECT OF COOPERATIVE LEARNING JIGSAW TYPE TO INCREASE LEARNING RESULT OF BASIC BIOMEDICAL LECTURE - ita ainun jariyah; asef wildan munfadlila (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Students are an active part that plays a role in the learning process. Cooperative learning trains students to be able to work together and responsibly independently. This research was quasi-experimental research with posttest-only control design. The sample of this research was the students of Diploma III Nursing STIKes Bina Sehat PPNI Mojokerto at the level I of academic year 2017/2018. The research data was obtained from the result of the final examination of the students in the basic biomedical course. The data were analyzed using independent sample t-test. The result of the independent sample t-test is 0.00 is less than 0.05. The conclusion of these results is that there are differences in basic biomedical learning outcomes in the control class and experimental class. Average learning outcomes control class 60,17 and experimental class 73,94. These results suggest that jigsaw type cooperative learning can improve student learning outcomes in basic biomedical courses.